PREGNANT MOTHERS' PERCEPTION OF PREGNANT MOTHERS' PERCEPTION OF INTEGRATED ANTENATAL CARE SERVICES IN THE BRAGOLAN HEALTH CENTER AREA, BANYURIP DISTRICT, PURWOREJO REGENCY: PREGNANT MOTHERS' PERCEPTION OF INTEGRATED ANTENATAL CARE SERVICES IN THE BRAGOLAN HEALTH CENTER AREA, BANYURIP DISTRICT, PURWOREJO REGENCY - Tri Puspa Kusumaningsih (Jurnal Komunikasi Kesehatan, 2026)
Integrated ANC includes maternal neonatal tetanus elimination (MNTE), anticipation of nutritional deficiencies in pregnancy, prevention of malaria in pregnancy (PMDK), prevention of mother-to-child HIV transmission (PMTCT), birth planning and prevention of complications (P4K), prevention and treatment of STIs/UTIs in pregnancy, elimination of congenital syphilis (ESK/CSE), and management of TB in pregnancy (TB-ANC), as well as dental health checks for pregnant women. Based on a preliminary study conducted in September 2025, there were 60 pregnant women who had Integrated ANC at the Bragolan Health Center. From the results of interviews with midwives. There was an MMR of 1 case, namely Pre-Eclampsia on the 16th day of childbirth and an IMR of 2 cases, namely DM. The total coverage of K1 at the Bragolan Health Center was 100%. This study aims to determine the perception of pregnant women about integrated antenatal care services at the Bragolan Health Center, Banyurip District, Purworejo Regency. This research method is a descriptive study with a cross-sectional method. The population in this study were pregnant women from TM 1, TM 2 and TM 3. The number of respondents was 30 people, the initial population in this study was 30 people, the sample in the study used total sampling with 30 respondents, the research data were presented in the form of frequency distribution and cross tabulation. The results of the study showed that the level of knowledge of respondents was good for 16 people (53.33%), sufficient for 9 people (30%) and lacking for 5 people (16.66%). The conclusion in this study is that the level of knowledge and attitudes of most respondents at the Bragolan Health Center is good. Suggestions from researchers for midwives to be able to continue to improve Integrated ANC services well and friendly to get a satisfactory and good value for the progress of the Bragolan Health Center.